PERSONNEL ADMINISTRATION COMPETENCIES OF SCHOOL ADMINISTRATORS BASED ON THE FOUR SUBLIME STATES OF MIND UNDER ROI ET PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Sompho, Paweena; Chanayotha, Porntiwa (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research article were 1) to study about personnel administration competencies of school administrators based on the Four sublime states of mind under Roi Et primary education service area office 2 2) To compare the opinions of school administrators and teachers on the personnel administration competencies of school administrators based on the Four sublime states of mind under Roi Et primary educational service area office 2, classified by position and school size3) to study the guidelines for developing competencies in personnel administration competencies of school administrators based on the Four sublime states of mind under the office of Roi Et primary education service area 2. The sample group in this research was 338 school administrators and teachers. The research instrument was questionnaire and semi-structured. The statistics used were frequency, percentage, mean, and standard deviation, t-test and one-way analysis of variance F-test (One-Way ANOVA). The results found that: 1) Personnel administration competencies of school administrators based on the four sublime states of mind under Roi Et primary educational service area office 2, the overall level was at a high level. The aspect with the highest average were planning, recruitment, personnel appointment, followed by treatment, promote discipline and punishment, and the aspect with the lowest average was promotion of honor. 2) The comparison results of personnel administration competencies of school administrators based on the four sublime states of mind under Roi Et primary educational service area office 2, classified by position, school size. The difference was statistically significant at the .05 level. 3) The summary of guidelines for personnel administration competencies of school administrators based on the four sublime states of mind. It was found that policies and plans should be established to allocate power rate according to the workload framework clearly defined to allocate. Recruitment channels should be to match the current age and the target group, and report information to the office of educational service area about the rate of power objectively.